A 1-kHz Single Frequency Nd:YAG Ring Laser by Injection Seeding*Supported by the National Key Research and Development Program of China under Grant No 2017YFB1104500, and the National Natural Science Foundation of China under Grant No 61875100. (December 2019) - Cao 曹, Xue-Zhe 雪喆; Li 李, Pei-Lin 沛霖; Wang 王, Zai-Yuan 在渊; Liu 柳, Qiang 强
Abstract : We report on an injection seeded 1 kHz single frequency pulsed Nd:YAG ring laser with pulse energy of 5.2 mJ and pulse width of 9.9 ns. The ramp-fire technique is used to maintain single frequency operation and the cavity length is modulated by an intracavity RbTiOPO 4 (RTP) crystal. The frequency stability (rms) of the output pulse is 1.99 MHz over 1 min and the linewidth is 64 MHz .